Effectiveness of Village Financial Management: The Roles of Financial Literacy, Internal Supervision & Leadership Style - Risdayani, Risdayani; Rasyid, Rosyeni; Yanuarta, Ramel (Ilomata International Journal of Management, 2026)
Village financial management is a crucial factor for realizing accountable and effective local development. This study examines the effects of financial literacy, internal supervision, and leadership style on the effectiveness of village financial management in the Anambas Islands Regency. Data were collected from a survey of 279 village officials (village heads, members of the Village Consultative Body [BPD], and village administrative staff) across 52 villages. The 28-item instrument was tested for validity and reliability and exhibited high internal consistency (Cronbach’s α). Because normality tests indicated non-normal distributions for the main variables, inferential analysis employed the nonparametric Mann–Whitney U test to evaluate six hypotheses concerning direct effects and inter-variable relationships. Empirical results indicate that financial literacy, internal supervision, and leadership style each have no significant effect on the effectiveness of village financial management; likewise, no significant relationships were found between literacy and supervision, supervision and leadership style, or literacy and leadership style. These findings likely reflect a knowledge–action gap and conceptual mismatches between indicators that measure declarative knowledge and outcomes that are administrative-instrumental; furthermore, supervision as measured emphasizes procedural formality and leadership constrained by collective regulation, which may weaken causal links. Policy implications stress the need for applied training interventions, enhancement of supervisors’ technical capacity, and institutional reforms to better integrate technical inputs into decision-making. Future research is recommended using mixed-methods designs, measurement of relevant subdimensions, and multilevel or intervention studies to test mechanisms for translating knowledge into practice.